2021
DOI: 10.1161/jaha.121.023517
|View full text |Cite
|
Sign up to set email alerts
|

PRRX1 Loss‐of‐Function Mutations Underlying Familial Atrial Fibrillation

Abstract: Background Atrial fibrillation (AF) is the most common form of clinical cardiac dysrhythmia responsible for thromboembolic cerebral stroke, congestive heart failure, and death. Aggregating evidence highlights the strong genetic basis of AF. Nevertheless, AF is of pronounced genetic heterogeneity, and in an overwhelming majority of patients, the genetic determinants underpinning AF remain elusive. Methods and Results By genome‐wide screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 84 publications
0
17
0
1
Order By: Relevance
“…Notably, in PRRX1 -knockout mice, cardiovascular developmental malformations occurred, encompassing awkward curvature and abnormal positioning of the aortic arch, an aberrant retro-esophageal right subclavian artery as well as a misdirected and elongated ductus arteriosus, highlighting the crucial role of PRRX1 in the proper development of vessels and perivascular matrices ( Bergwerff et al , 2000 ). Moreover, a recent study has demonstrated that PRRX1 physically binds to the promoters of SHOX2 and ISL1 and transcriptionally activates the expression of SHOX2 and ISL1 ( Guo et al , 2021 ), two key downstream target genes responsible for the normal development of the heart, especially for its pacing and conducting system ( Blaschke et al , 2007 ; Liang et al , 2015 ; Vedantham et al , 2015 ; Galang et al , 2020 ) and variations in both SHOX2 and ISL1 have been causally linked to AF and CHD ( Blaschke et al , 2007 ; Hoffmann et al , 2016 , 2019 ; Li et al , 2018 ; Ma et al , 2019 ; Wang et al , 2019 ; Wu et al , 2020 ). In the present research, a new PRRX1 loss-of-function variation was discovered to lead to AF and PDA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, in PRRX1 -knockout mice, cardiovascular developmental malformations occurred, encompassing awkward curvature and abnormal positioning of the aortic arch, an aberrant retro-esophageal right subclavian artery as well as a misdirected and elongated ductus arteriosus, highlighting the crucial role of PRRX1 in the proper development of vessels and perivascular matrices ( Bergwerff et al , 2000 ). Moreover, a recent study has demonstrated that PRRX1 physically binds to the promoters of SHOX2 and ISL1 and transcriptionally activates the expression of SHOX2 and ISL1 ( Guo et al , 2021 ), two key downstream target genes responsible for the normal development of the heart, especially for its pacing and conducting system ( Blaschke et al , 2007 ; Liang et al , 2015 ; Vedantham et al , 2015 ; Galang et al , 2020 ) and variations in both SHOX2 and ISL1 have been causally linked to AF and CHD ( Blaschke et al , 2007 ; Hoffmann et al , 2016 , 2019 ; Li et al , 2018 ; Ma et al , 2019 ; Wang et al , 2019 ; Wu et al , 2020 ). In the present research, a new PRRX1 loss-of-function variation was discovered to lead to AF and PDA.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant eukaryotic expression plasmid PRRX1 -pcDNA3.1 expressing human wild-type PRRX1 was constructed as previously described ( Guo et al , 2021 ). The Glu125 * -mutant PRRX1 -pcDNA3.1 was generated by site-targeted mutagenesis utilizing a complimentary pair of primers (forward primer: 5'-GATGCTTTTGTGCGATAAGACCTTGCCCGCC-3'; reverse primer: 5'-GGCGGGCAAGGTCTTATCGCACAAAAGCATC-3') and a site-directed mutagenesis kit (Stratagene, USA) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations